Analisis perencanaan, penggunaan dan penatausahaan aset tetap pada Dinas Perindustrian dan Perdagangan Provinsi Sulawesi Utara - Kastilong, Verentio Gregorius; Afandi, Dhullo; Latjandu, Lady Diana (Yayasan Widyantara Nawasena Raharja, 2025)
Fixed assets represent a crucial component of public sector resource management because they support the operational activities of government agencies in carrying out their duties and functions. This study analyzes the planning, utilization, and administration of fixed assets at the Department of Industry and Trade of North Sulawesi Province and evaluates their compliance with the applicable regulations. Using a qualitative descriptive approach through interviews and document analysis, the research assesses the implementation of fixed asset management practices. The findings show that the planning and utilization of fixed assets have been carried out in line with Minister of Home Affairs Regulation (Permendagri) No. 19 of 2016 as amended by Permendagri No. 7 of 2024. In addition, the administration of fixed assets—including recording, inventory, and reporting—conforms to Permendagri No. 47 of 2021. These results indicate that systematic planning, proper utilization, and accurate administration of fixed assets can enhance transparency, accountability, and efficiency in local government financial management.